Nutritional status as predictors for quality of life among caregivers of children with severe cerebral palsy - Kamal, Sakinah; Hamzaid, Nur Hana; Kamaralzaman, Sazlina; Sharma, Shobha; Jaafar, Nurul Hazirah; Chern, Phei Ming; Hassan, Nurul Izzaty; Toran, Hasnah; Ismail, Noor Akmal Shareela; Yusri, Ghazali (AME Publishing Company, 2023)
Background: Individuals with severe cerebral palsy (CP) often experience various health issues, including feeding difficulties, which can adversely affect their nutritional status and caregivers’ quality of life, e.g., more time spent for feeding rather than own selfcare. This study aimed to determine the prevalence of poor nutritional status among individuals with severe CP and explore its role as predictors for caregivers’ quality of life. Methods: This cross-sectional study was conducted in a government hospital (Cheras Rehabilitation Hospital), Community-Based Rehabilitation (CBR) Program, and Spastic Centre [non-profit organization (NGO)] in Klang Valley, Malaysia. Seventy-one participants with Gross Motor Function Classification System (GMFCS) level IV and V were recruited. Sociodemographic data, health-associated data, and anthropometric data were collected. Caregivers’ quality of life was assessed using the Pediatric Quality of Life Inventory (PedsQL) CP module version 3.0 which included domains such as Movement and Balance, Eating Activities, and School Activities. Results: Most participants were males (60.6%), with 61 classified as level IV in the GMFCS classification. According to the Eating and Drinking Ability Classification System (EDACS), 59 children were at level IV. In total, 40.8% were underweight according to CP growth chart and 49.3% had mid-upper arm circumference (MUAC) readings below the 5th percentile. The lowest scores in the PedsQL CP module version 3.0 were observed in the Daily Activities (5.34±10.87), and School Activities domains (8.15±18.65). Sociodemographic and anthropometric data, including body mass index (BMI)-for-age, MUAC, body fat, triceps, and subscapular skinfold measurement, were predictors for the School Activities domain [F (11, 44)=3.981, P<0.005, R2=0.499]. Conclusions: Poor nutritional status in individuals with severe CP has been shown to negatively impact caregivers’ quality of life. Therefore, a multidisciplinary approach involving nutritional intervention is essential to improve dietary provision and the nutritional status of children with CP.